A model for dip-coating of a two liquid mixture - S. B. G. O'Brien; M. Hayes (International Journal of Mathematics and Mathematical Sciences)
We consider a thin film flow where a flat substrate is coated with a mixture of two miscible liquids, of equal viscosity, and develop a model to predict the evolving coating thicknesses. The developed model can, under certain circumstances, be used as an approximation for the dip-coating of a liquid suspension of a viscous volatile liquid and solid solute as occurs in many industrial applications.